Relationship between the dinoflagellate cyst Spiniferites pachydermus and Gonyaulax ellegaardiae sp. nov. from Izmir Bay, Turkey, and molecular characterization. Issue 3 (20th May 2015) - Mertens, Kenneth Neil; Aydin, Hilal; Uzar, Serdar; Takano, Yoshihito; Yamaguchi, Aika; Matsuoka, Kazumi; Lin, S.
<x xml:space="preserve">Abstract</x> Here, we established the cyst‐motile stage relation‐ship for Spiniferites pachydermus through incubation of cysts with a characteristically microreticulate/perforate surface isolated from Izmir Bay in the eastern Aegean Sea of the eastern Mediterranean. The morphology of the motile stage was similar to Gonyaulax spinifera but had a different size, overhang, displacement and reticulations. Based on the distinct morphology of the cyst and morphological differences in motile cells, we assigned S. pachydermus from Izmir Bay to the new species Gonyaulax ellegaardiae. We elucidate the phylogenetic relationship of G. ellegaardiae through large and small subunit ribosomal DNA and show that it forms a clade with other species that belong to the G. spinifera complex.